A brain proteome profile in rats exposed to methylmercury or thimerosal (ethylmercury). Issue 12 (17th June 2016) - de Oliveira Souza, Vanessa Cristina; de Marco, Kátia Cristina; Laure, Hélen Julie; Rosa, José Cesar; Barbosa, Fernando
ABSTRACT: Exposure to organomercurials has been associated with harmful effects on the central nervous system (CNS). However, the mechanisms underlying organomercurial-mediated neurotoxic effects need to be elucidated. Exposure to toxic elements may promote cellular modifications such as alterations in protein synthesis in an attempt to protect tissues and organs from damage. In this context, the use of a "proteomic profile" is an important tool to identify potential early biomarkers or targets indicative of neurotoxicity. The aim of this study was to investigate potential modifications in rat cerebral cell proteome following exposure to methylmercury (MeHg) or ethylmercury (EtHg). For MeHg exposure, animals were administered by gavage daily 140 µg/kg/d of Hg (as MeHg) for 60 d and sacrificed 24 h after the last treatment. For EtHg exposure, 800 µg/kg/d of Hg (as EtHg) was given intramuscularly (im) in a single dose and rats were sacrificed after 4 h. Control groups received saline either by gavage or im. After extraction of proteins from whole brain samples and separation by two-dimensional electrophoresis (2-DE), 26 differentially expressed proteins were identified from exposed animals by matrix-assisted laser desorption ionization–time of flight (MALDI-TOF/TOF). Both MeHg and EtHg exposure induced an overexpression of calbindin, a protein that acts as a neuroprotective agent by (1) adjusting the concentration of Ca 2+ within cells and preventing neurodegenerative diseases and (2) decreasing expression of glutamine synthetase, a crucial protein involved in regulation of glutamate concentration in synaptic cleft. In contrast, expression of superoxide dismutase (SOD), a protein involved in antioxidant defense, was elevated in brain of MeHg-exposed animals. Taken together, our data provide new valuable information on the possible molecular mechanisms associated with MeHg- and EtHg-mediated toxicity in cerebral tissue. These observed protein alterations may be considered as biomarkers candidates for biological monitoring of organomercurial poisoning.